(untitled) (Educação e Pesquisa, 2022)
In this research, tools of the Ontosemiotic Approach (OSA) were used to analyse the formative experience of two teachers in Primary Education service, guided towards the design and implementation of tasks for mobile learning, based on the meaning of the natural number and the use of Kahoot. The experience was developed during a workshop on the design of interactive lessons, where teachers were trained on the use of Kahoot for the design of mathematical content and its implementation in a real class context. Didactic engineering in the general sense of OSA was used as a methodological element. Specifically, the case of the design and implementation of an interactive lesson on the meaning of number sequence was analysed, where some results of the retrospective analysis of the formative experience indicated that: 1) the reference meaning of the natural number is a tool that allows to guide the design of tasks towards the partial meanings, the identification of primary objects, and the Ontosemiotic analysis of them; 2) the use of mobile devices and Kahoot together motivated the teachers. With these results, two training actions are proposed, aimed at teachers: 1) the design of mobile content from the reference meaning of the natural number, and 2) the assessment of the didactic suitability of teaching experiences mediated by mobile devices.